2020
DOI: 10.1186/s12870-020-2298-5
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of RopGEF gene family to identify genes contributing to pollen tube growth in rice (Oryza sativa)

Abstract: Background: In plants, the key roles played by RopGEF-mediated ROP signaling in diverse processes, including polar tip growth, have been identified. Despite their important roles in reproduction, a comprehensive analysis of RopGEF members has not yet been performed in rice (Oryza sativa). To determine whether RopGEF regulators are involved in rice pollen tube growth, we performed genome-wide analysis of this family in rice. Results: Phylogenomic and meta-expression analysis of eleven RopGEFs in rice showed tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 63 publications
3
28
1
Order By: Relevance
“…Arabidopsis encodes three pollen‐specific ROP genes ( ROP1 , ROP3 and ROP5 ), and ROP1 is a central regulator of polar PT growth via regulation of F‐actin dynamics and apical exocytosis (Gu et al ., 2003; Luo et al ., 2017). Recently, we found that rice has one ROP gene showing a high expression level in pollen, namely Rac6 , which is also ubiquitously expressed in other rice tissues (Kim et al ., 2020a). The difference in the expression patterns of ROP genes between the two species may cause distinct regulation by REN4 and GORI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arabidopsis encodes three pollen‐specific ROP genes ( ROP1 , ROP3 and ROP5 ), and ROP1 is a central regulator of polar PT growth via regulation of F‐actin dynamics and apical exocytosis (Gu et al ., 2003; Luo et al ., 2017). Recently, we found that rice has one ROP gene showing a high expression level in pollen, namely Rac6 , which is also ubiquitously expressed in other rice tissues (Kim et al ., 2020a). The difference in the expression patterns of ROP genes between the two species may cause distinct regulation by REN4 and GORI.…”
Section: Discussionmentioning
confidence: 99%
“…The rupo PTs also burst precociously in vivo and in vitro (Liu et al, 2016), suggesting that conserved mechanisms of RLK-mediated signaling are involved in the cell wall integrity of PTs. Recently, we identified four pollen-specific Rop-GEF genes in rice; the RopGEF2/-8 double mutant exhibited partial sterility owing to a reduced pollen germination ratio (Kim et al, 2020a) whereas the single mutant exhibited no significant difference in fertility. Similarly, Arabidopsis showed a PT defect in the quadruple mutants, suggesting their redundant ROP regulatory function (Chang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…RopGEFs were then proposed as integration points for guidance cues, as an increased activation of Rop1 in response to a guidance cue would cause the shift in Rop1 activity and re-direction of secretion [ 12 ]. Consequently, RopGEFs, RhoGAPs, and RhoGDIs are important modulators of pollen tube growth due to their regulation of Rop/Rac GTPases [ 124 , 136 , 148 , 149 , 150 ]. Thus, male transmission defects were observed when RhoGDI function was missing in Arabidopsis [ 149 ].…”
Section: Small Gtpases Define the Pollen Tube Tipmentioning
confidence: 99%
“…The molecular function of RopGEF and ROP/Rac in root hair growth of other plants is less known. There are 11 OsRopGEFs and 7 OsRac genes in rice (Miki et al, 2005;Kim et al, 2020). The functions of control grain size, RNA silencing, apoptosis regulation, and gene expression in OsRacs have been studied (Kawasaki et al, 1999;Miki and Shimamoto, 2004;Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The functions of control grain size, RNA silencing, apoptosis regulation, and gene expression in OsRacs have been studied (Kawasaki et al, 1999;Miki and Shimamoto, 2004;Zhang et al, 2019). Phylogenetic analysis and expression profiles suggest different features of ROP between Arabidopsis and rice (Kim et al, 2020). However, it has not been elucidated how OsRopGEF and OsRac regulate root hair development in rice, a model crop plant.…”
Section: Introductionmentioning
confidence: 99%